The Thanatomicrobiome: A Missing Piece of the Microbial Puzzle of Death - Javan, Gulnaz T.; Finley, Sheree J.; Abidin, Zain; Mulle, Jennifer G. (Frontiers in Microbiology, 2016)
Death is a universal phenomenon; however, is there “life after death?” This topic has been investigated for centuries but still there are grey areas that have yet to be elucidated. Forensic microbiologists are developing new applications to investigate the dynamic and coordinated changes in microbial activity that occur when a human host dies. There is currently a paucity of explorations of the thanatomicrobiome (thanatos-, Greek for death) and epinecrotic communities (microbial communities residing in and/or moving on the surface of decomposing remains). Ongoing studies can help clarify the structure and function of these postmortem microbiomes. Human microbiome studies have revealed that 75-90% of cells in the body prior to death are microbial. Upon death, putrefaction occurs and is a complicated process encompassing chemical degradation and autolysis of cells. Decomposition also involves the release of contents of the intestines due to enzymes under the effects of abiotic and biotic factors. These factors likely have predictable effects on postmortem microbial communities and can be leveraged for forensic studies. This mini review provides a critical examination of emerging research relating to thanatomicrobiome and epinecrotic communities, how each is studied, and possible strategies of stochastic processes.